STUDI PERENCANAAN TEBAL LAPISAN TAMBAHAN (OVERLAY) PADA RUAS JL. PANGLIMA SUDIRMAN KECAMATAN KEPANJEN KABUPATEN MALANG (STA 0+0.00-0+1.000 M) - Paningsih, Esol; Primasworo, Rifky Aldila (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2019)
Roughness of the road is a system composed of several layers of material that is placed on the land-base (subgrade).Construction of elastic roughness (flexible pavement) consists of four layers, namely the surface layer (surface course), the upper layers of the Foundation (base course), a layer of Foundation bottom (subbase course), the basic soil Layer (subgrade).The main objective of the building of roughness is to provide a flat surface with skid resistance, with fairly long service lifespan, as well as minimum maintenance. To smooth the roughness is done.This road roughness along 1 km with an average width of 7,5 m in this study the author discusses the planning process calculation of thick layer (overlay) by using a method of analysis of the components of the Department of public works, based on the results of the calculation, obtained the order of thick layer (overlay) consists of the Foundation of the baw ah (Sub Base) 20 cm thick, Foundation top (Base Course) 15 cm thick, long layer surface (Surface) 5 cm. And obtained that the surface layer (overlay) approx 6 cm type of Asphalt Macadam with age plan 10 year and the growth rate of traffic gained 1% per year.